A randomised controlled trial of a home based exercise programme to reduce the risk of falling among people with Parkinson's disease. Issue 7 (21st November 2006) - Ashburn, Ann; Fazakarley, Louise; Ballinger, Claire; Pickering, Ruth; McLellan, Lindsay D; Fitton, Carolyn
Abstract : Objective: To evaluate the effectiveness of a personalised home programme of exercises and strategies for repeat fallers with Parkinson's disease (PD). Method: Patients with a confirmed diagnosis of idiopathic PD, independently mobile, living at home in the community, experiencing more than one fall in the previous 12 months and with intact gross cognitive function were invited to participate in this randomised controlled trial. Usual care was compared with a personalised 6 week, home based exercise and strategy programme. The primary outcomes were rates of falling at 8 weeks and 6 months. Whether participants had repeat fallen, nearly fallen or experienced injurious falls were also examined. Functional Reach, the Berg Balance Test, PD Self-assessment Scale and the Euro Quol were rated by a blinded assessor. Results: Participants were randomised to the exercise (n = 70) and control (n = 72) groups. There was a consistent trend towards lower fall rates in the exercise group at both 8 weeks and 6 months and lower rates of injurious falls needing medical attention at 6 months. Lower rates of repeat near falling were evident for the exercise group at 8 weeks (p = 0.004) and 6 months (p = 0.007). There was a positive effect of exercises at 6 months on Functional Reach (p = 0.009) and quality of life (p = 0.033). No significant differences were found on other secondary outcomes measures. Conclusion: There was a trend towards a reduction in fall events and injurious falls with a positive effect of exercises on near falls and quality of life.